Ignacio M. Sánchez Prado, editor. Mexican Literature as World Literature. Bloomsbury Academic, 2022. - Caroline E Tracey (Studies in 20th & 21st Century Literature, 2023)
Review of Ignacio M. Sánchez Prado, editor. Mexican Literature as World Literature. Bloomsbury Academic, 2022. 266 pp.
Keywords: Mexico; world literature